Preparation, Characterization, and Wound Healing Activity of Papaya Leaves Extract on Spray Gel - Dina Permata Wijaya; Herlina Herlina; Najma Annuria Fitri; Mardiyanto Mardiyanto; Mustikasanti Mustikasanti; Firnando Firnando (Majalah Obat Tradisional, 2020)
Papaya leaves have been using for wound healing that contains flavonoids, saponins, phenolics, chymopapain, and papain enzymes. The aim of this research were preparation, characterization, and wound healing activity of papaya leaves extract on spray gel. Spray gel was formulated with variation of gelling agent such as carbopol 940, HPMC, gellan gum, and hydroxyethylcellulose. The spray gel were characterizated by organoleptic, pH, stickiness test, viscosity, homogeneity, weight, and wound healing activity in rats. The results showed were all of formula spray gel have brown and homogeneous, pH between 5,947-6,347 within pH range of skin, stickiness test between 1,92-8,12 s, viscosity between 880-1740 cPs. Papaya leaves extract on spray gel has wound healing activity in rats faster than extract and positive control that is 16 days. The wound healing of papaya leaves extract on spray gel exhibited significantly different (p<0,05) than negative control.